Pengaruh Fluktuasi Volume Penumpang Berdasarkan Kategori Hari terhadap Pola Operasi LRT Jabodebek - Agus Nugroho; Haniva Mulyani; Dedek Nurannisa; Heriyanto Wibowo; Sinung Tri Nugroho (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study analyzes the impact of differences in passenger volume between weekdays and weekends on the operational patterns of the Jabodebek Light Rail Transit (LRT). The research aims to understand how fluctuations in passenger numbers influence service scheduling and resource allocation for urban mass transportation efficiency. Research Methodology: A quantitative approach was employed using descriptive analysis and non-parametric statistical testing to evaluate passenger volume data. The analysis focused on the period from November 2024 to April 2025. The Mann-Whitney U test was applied to compare weekday and weekend passenger volumes, which were found to fluctuate significantly—exceeding 50% differences between the two periods. Results: Statistical calculations revealed that the Mann-Whitney U test value was 0.000 (assumed 0.0001) with a Z-score of -11.221, and the significance value (Asymp. Sig 2-tailed) was also 0.000 (<0.05). These results indicate that the difference in passenger volume between weekdays and weekends is statistically significant. Conclusions: The findings highlight that the LRT Jabodebek operation pattern must differentiate between weekday, weekend, and special event (e.g., New Year’s Eve, national football matches) schedules to align with fluctuating passenger volumes. Limitations: The research was limited to six months of passenger data, which may not capture annual seasonal variations or special public holidays. Contribution: This study contributes to the understanding of how passenger volume fluctuations influence operational patterns in urban mass transport systems. It offers practical recommendations for operators to design adaptive and cost-efficient service schedules that enhance service quality and passenger satisfaction.